Technical Efficiency Analysis with a Frontier Approach in Milkfish Farming in Demak Regency - Suparjo, Suparjo; Gozali, Imam (International Journal of Supply Chain Management, 2020)
This study aims to analyze the factors that influence the level of production and the level of production efficiency of the milkfish pond farming in Demak Regency, Central Java Province, Indonesia. The research sample was 160 milkfish farmers who were selected by survey method through interviews with respondents using structured questionnaires to obtain primary data. Data analysis used stochastic frontier production function analysis. The results of the research analysis showed that the production factors of land area, milkfish seeds, feed, labor, and fertilizer had a significant effect on production yields. Lime production factor has no significant effect on production yield. The average technical efficiency of milkfish pond farming is 0.69. The production of milkfish pond culture is technically not efficient, but it is worth cultivating. This study suggests that improving technical efficiency can be done by optimizing the milkfish pond farmers' production factors which significantly affect production yields.